2012
DOI: 10.3329/jbas.v36i2.12971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Terminal Bud Pinching On Growth and Yield of Chrysanthemum, Chrysanthemum Indicum L.

Abstract: An experiment on pinching (viz. P 0 ; without pinching and P 1 ; with pinching) with 3 replications showed the tallest (37.7 cm) and the shortest plant (33.4 cm) without pinching and with pinching, respectively. Maximum number of leaves (30.1) and flowers (58.7) per plant were recorded following pinching (P 1 ); and minimum number of leaves (26.8) and flowers (37.9) per plant were from without pinching (P 0 ).Key words: Pinching, Chrysanthemum indicum, Flower, Terminal bud, Growth, Yield Chrysanthemum (Chrysan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
2
3
0
2
Order By: Relevance
“…Since hormone balance is presumably important to the overall effect on growth and morphological changes. By removing the shoot apex auxins concentration reduces that hampers upward plant growth and the lateral shoots trigger to grow as a result the number of branches as well as the number of leaves increased (Habiba et al, 2012). The current finding is also in line with those of Ali et al (2021), Ona et al (2015) and Sharaf-Eldien et al (2017), who documented that removal of the shoot apex in several ornamental plants increased the number of leaves plant -1 .…”
Section: A Assessment Of Vegetative Parameterssupporting
confidence: 89%
“…Since hormone balance is presumably important to the overall effect on growth and morphological changes. By removing the shoot apex auxins concentration reduces that hampers upward plant growth and the lateral shoots trigger to grow as a result the number of branches as well as the number of leaves increased (Habiba et al, 2012). The current finding is also in line with those of Ali et al (2021), Ona et al (2015) and Sharaf-Eldien et al (2017), who documented that removal of the shoot apex in several ornamental plants increased the number of leaves plant -1 .…”
Section: A Assessment Of Vegetative Parameterssupporting
confidence: 89%
“…In case of controlled (un-treated) plants produced less number of leaves (54.8) plant -1 . Habiba et al (2012) observed more leaves plant -1 after pinching Chrysanthemum indicum. Naresh and Singh (2012) reported that plants (African marigold) that were pinched produced maximum leaves plant -1 .…”
Section: Number Of Leaves Plant -1mentioning
confidence: 83%
“…Terminal buds producing natural auxin were removed which enhanced number of branches plant -1 in chrysanthemum flower. With removing the terminal buds reduces auxins concentration that hampers upward plant growth and the lateral buds starts to sprout as a result number of branches increases (Habiba et al, 2012). Eraki (1994) also found increased branches plant -1 with foliar application of BAP on Hibiscus.…”
Section: Number Of Branches Plant -1mentioning
confidence: 98%
“…Variabel jumlah bunga per tanaman pada perlakuan pinching (P1) menghasilkan jumlah bunga yang lebih banyak daripada perlakuan non pinching (P0). Penelitian Habiba et al (2012) pada tanaman krisan, bahwa tunas samping membantu dalam mencapai pertumbuhan vegetatif yang optimal tanpa mengganggu pertumbuhan tanaman krisan yang normal. Ini bisa menjadi hasil dari distribusi yang lebih merata dari asimilasi antara beberapa titik tumbuh (dalam cabang aksila) daripada hanya yang apikal (seperti pada tanaman kontrol).…”
Section: Jumlah Bunga Per Tanamanunclassified